Inhibition of autophagy using 3-methyladenine increases cisplatin-induced apoptosis by increasing endoplasmic reticulum stress in U251 human glioma cells - ZHANG, RUIJIAN (D.A. Spandidos, 2015)
Cisplatin is one of the most widely used chemotherapeutic drugs; however, the side effects and drug resistance limit its usage. Previous findings have demonstrated that cisplatin kills tumor cells through endoplasmic reticulum (ER) stress, which provides a novel method to minimize cisplatin toxicity and circumvent cisplatin resistance. ER stress induces cell autophagy, cell apoptosis and the complicated regulatory network between them. The role of autophagy in cisplatin chemotherapy remains to be elucidated. 3-Methyladenine (3-MA) is normally used as an inhibitor of autophagy. The present study reveals a significant role of the inhibition of autophagy by treatment with 3-MA and cisplatin in combination in U251 human glioma cells. It was demonstrated that cisplatin induced the ER stress associated with apoptosis and autophagy in U251 cells. Inhibition of autophagy by 3-MA increased the expression levels of protein disulfide isomerase, ubiquitinated proteins, glucose regulated protein 78 and CCAAT-enhancer-binding protein homologous protein, and induced the activation of caspase-4 and caspase-3. Treatment with 3-MA combined with cisplatin increased cisplatin-induced apoptosis by increasing ER stress. Therefore, the inhibition of autophagy has the potential to improve cisplatin chemotherapy.